Sosialisasi Komunikasi Penyuluhan Pertanian Bersama Mahasiswa - Maihani, Syarifah; Nur, T.M.; Rahmi, Eka; Mariana, Mariana; Ahmad Zaki, Sayed; Afrinanda, Cut (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
Lancok Village is one of the villages in Peusangan District, Bireuen Regency. This village is the location for Community Service (PKM) activities. Students who are members of the PKM team from the Faculty of Agriculture, Agribusiness Study Programme, Almuslim University. The majority of Acehnese people work as farmers. So, we, who are students of the Faculty of Agriculture, Almuslim University, aim to carry out community service by socializing agricultural extension activities with Bireuen district extension officers to find out communication studies in agriculture, where the messages conveyed are agricultural messages, either in the form of new information, new ideas, new technology, or improvements to new methods. This extension was carried out on 23 May 2024 by specifically inviting the Extension Officer as the party who would present the extension material. As a result of this outreach, agricultural students get a space to voice their opinions about various agricultural problems that they hear and see in the field. One of the participants and representatives of agrarian students thought that this extension activity was very good because in addition to adding insight, the material presented was also related to the main problems often faced by farmers.